Tubos de concreto com adição de resíduos de borracha de pneu - Queiroz, Rodolfo Mori [UNESP] (2012)
The concrete pipes with diameters greater than 400 mm are used in culverts, crossings, rainwater drainage, sanitary sewer and plumbing supply. The tire rubber residues are being applied to various purposes such as: alternative fuel for the cement industry, in the manufacture of shoe soles in rubber seals, rainwater pipes, flooring for sports courts, industrial floors, asphalt-rubber mats for automobiles and various types of concrete. The tire rubber residue, when added to concrete, may improve some properties such as impermeability, flexibility, abrasion resistance and corrosion resistance. In another context, incorporation in the concrete of these residues appears as a possibility to mitigate environmental impacts, especially knowing that it is generated abundantly during the retreading process. It is noted, however, that the inclusion of this residue may lead to a decrease in compressive strength and modulus of elasticity. Based on standard NBR 8890 (ABNT, 2007), this research aims to analyze the mechanical behavior of prototypes of concrete pipes made with different contents of additions of tire rubber residue, such as: 10 kg/m³, 15 kg/m³, 20 kg/m³, 25 kg/m³ and 30 kg/m³. The concrete pipes that were studied had nominal diameter of 600 mm and length of 1.5 m, being intended for drainage systems of rainwater. The concrete pipes in real scale were submitted to the test of diametral compression strength and, after their ruptures, to the water absorption test, which samples were collected from the broken pieces. The results obtained by the diametral compression test were satisfactory since all pipes made with the mixtures exceeded the minimum value of the brazilian standard, but the tire rubber residue did not behave as a fiber. The content of 15 kg of tire rubber residue per cubic meter of concrete was the one who had the best performance. The addition of tire rubber residue had not changed the characteristic of concrete related to ...